Toss a stablecoin to your banker: Stablecoins' impact on banks' balance sheets and prudential ratios - Charles-Enguerrand Coste (European Central Bank (ECB), 2024)
This paper explores the relationship between banks and stablecoins and their issuers, focusing on the mechanical effects on banks' capital and liquidity ratios when issuing stablecoins or collecting deposits from stablecoin issuers. The analysis reveals that converting retail deposits into stablecoin issuers' deposits weakens a bank's liquidity coverage ratio (LCR), turning a retail deposit into a wholesale deposit, even when these funds are reinvested in high-quality liquid assets. If a credit institution issues its own stablecoins, the impact on its LCR depends on whether it can identify the stablecoin holders; unknown holders weaken the LCR which could incentivise banks to issue stablecoins where they can continually identify the holders to benefit from more favourable liquidity treatment. Additionally, banks must either hold the reserves backing the stablecoins as central bank reserves or reinvest them in low-risk assets, making these funds a less effective source for economic financing and maturity transformation compared with traditional retail deposits. The study also finds that when retail customers of bank A buy a stablecoin issued by a non-bank that keeps reserves at bank B, both banks could see an unexpected decline in their liquidity ratios, as bank A loses stable retail deposits and bank B gains volatile wholesale deposits. These insights are crucial to understanding the dynamics between banks and stablecoins in the evolving financial landscape.
Keywords: E40; E42; E49; G11; G15; G18; G20; G21; G23; G28; 330; stablecoin; e-money; crypto-asset; MiCAR; bank; prudential regulation; bank's balance sheet